2003
DOI: 10.1051/0004-6361:20030850
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of the Kuiper-Belt object 1999 TD$_{\sf\sl 10}$ at different phase angles

Abstract: Abstract. We present photometric observations of the Kuiper-Belt object 1999 TD 10 at different phase angles and for three different broad band filters (B, V and R). This object was observed with the Danish 1.54-m telescope of ESO in Chile during six different observing nights corresponding to a phase angle of 0. 30, 0.37, 0.92, 3.43, 3.48 and 3.66 • . Extra observations were obtained in September 2002 with the VLT UT1/FORS1 combination to confirm that 1999 TD 10 does not exhibit any cometary activity, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 28 publications
(35 reference statements)
5
31
0
Order By: Relevance
“…If we assume a maximum difference in absolute magnitudes of 0.012 mag between the two runs, then the corresponding change in the derived solar phase coefficient β is 0.015 mag deg −1 which is of the same order as the error of β quoted above. R 0 is consistent with R opp derived by Choi et al (2003) and H R by Rousselot et al (2003). …”
Section: Solar Phase Dependencesupporting
confidence: 87%
See 3 more Smart Citations
“…If we assume a maximum difference in absolute magnitudes of 0.012 mag between the two runs, then the corresponding change in the derived solar phase coefficient β is 0.015 mag deg −1 which is of the same order as the error of β quoted above. R 0 is consistent with R opp derived by Choi et al (2003) and H R by Rousselot et al (2003). …”
Section: Solar Phase Dependencesupporting
confidence: 87%
“…Their derivation is also widely different from the range of linear solar phase coefficients for seven TNOs by Sheppard and Jewitt (2002). The derived phase coefficient of β = 0.121 mag deg −1 by Rousselot et al (2003) is in agreement with the mean solar phase coefficient by Sheppard and Jewitt (2002). However, our mean absolute magnitudes in September 2001 and October 2002 using this coefficient are still inconsistent with each other.…”
Section: Solar Phase Dependencesupporting
confidence: 42%
See 2 more Smart Citations
“…Two TNOs have also been reported by some authors to have cometary activity. Choi et al (2003) reported cometary activity for the SDO (29981) 1999 TD 10 but other observations with larger telescopes (Rousselot et al 2003;Mueller et al 2004) detected nothing for this object. Hainaut et al (2000) presented a change in the lightcurve of the TNO (19308) 1996 TO 66 that could possibly be interpreted as the result of cometary activity.…”
Section: Introductionmentioning
confidence: 94%